Evidence for the long term cost effectiveness of home care reablement programs - Lewin, Gill; Alfonso, Helman; Alan, Janine (Dove Medical Press Ltd., 2013)
Background: The objectives of this study were to determine whether older individuals who participated in a reablement (restorative) program rather than immediately receiving conventional home care services had a reduced need for ongoing support and lower home care costs over the next 57 months (nearly 5 years). Materials and methods: Data linkage was used to examine retrospectively the service records of older individuals who had received a reablement service versus a conventional home care service to ascertain their use of home care services over time. Results: Individuals who had received a reablement service were less likely to use a personal care service throughout the follow-up period or any other type of home care over the next 3 years. This reduced use of home care services was associated with median cost savings per person of approximately AU $12,500 over nearly 5 years. Conclusion: The inclusion of reablement as the starting point for individuals referred for home care within Australia's reformed aged care system could increase the system's cost effectiveness and ensure that all older Australians have the opportunity to maximize their independence as they age.